Managing Pollution for Poverty Reduction and Green Development - World Bank Group (World Bank, Washington, DC, 2017)
The World Bank Group (WBG) has been active in public and private sector pollution management for the past several decades. The Bank has mainstreamed environmental health concerns into its rural and urban services through projects that improved the management of solid and hazardous waste and wastewater, and controlled pollution related to a large variety of sectors including transport, industry, energy, and mining, with each decade having its flagship issues and projects. The changing global context illustrated by the wave of global crises, the rising acknowledgement in different countries of the impacts of climate change and the necessity to address greenhouse gas mitigation, the challenges in reaching the Millennium Development Goals pertaining to environment and poverty, and the voices calling for new approaches through green new deal, green growth, and green development require that pollution management be addressed within a new context.